2011
DOI: 10.1186/1472-6955-10-9
|View full text |Cite
|
Sign up to set email alerts
|

High rates of burnout among maternal health staff at a referral hospital in Malawi: A cross-sectional study

Abstract: BackgroundBurnout among maternal healthcare workers in sub-Saharan Africa may have a negative effect on services provided and efforts to mitigate high maternal mortality rates. In Malawi, research on burnout is limited and no empirical research has been conducted specifically among maternal health staff. Therefore, the aims of the study were to examine the prevalence and degree of burnout reported by healthcare workers who provide antenatal, intrapartum, and postnatal services in a district referral hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
104
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 41 publications
(46 reference statements)
6
104
1
1
Order By: Relevance
“…High scores on EE and DP subscales correspond with high level of burnout, however, for PA subscale low scores correspond to high degree of experienced burnout. 6 The study was conducted according to the ethical guidelines of the College of Medicine and Health Sciences (CMHS) and the ethics clearance to conduct the study was offered by the Institutional Review Board of the same university and participating institution. Participants participated voluntary and provided informed consent in a written form and their right to withdraw from the research at any time were explained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High scores on EE and DP subscales correspond with high level of burnout, however, for PA subscale low scores correspond to high degree of experienced burnout. 6 The study was conducted according to the ethical guidelines of the College of Medicine and Health Sciences (CMHS) and the ethics clearance to conduct the study was offered by the Institutional Review Board of the same university and participating institution. Participants participated voluntary and provided informed consent in a written form and their right to withdraw from the research at any time were explained.…”
Section: Methodsmentioning
confidence: 99%
“…9 The factorial stability was evaluated in different cultures and countries and it was identified that it is useful in different nations with different languages and within different professions and occupations. 6 Therefore, this tool was used in this study without much rigorous testing especially because a translated version to French was also provided when permission was granted. Only a pilot study that involved three critical care nurses was conducted to exclude contextual issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Thorsen et al 2 in a study of high rates of burnout among maternal health staff in Malawi reported that 72% of their subjects reported emotional exhaustion, 43% reported depersonalization while 74% reported reduced personal accomplishment. They concluded that burnout appeared to be common among maternal health staff that participated in the study when compared with their colleagues working in other medical settings.…”
mentioning
confidence: 99%
“…When comparing nurses to physicians or other healthcare workers, nurses consistently reported higher levels of burnout. [2] NEED FOR THE STUDY Unfortunately, most of the studies on burnout in nursing have been conducted in Europe and United States. There are few studies from Asian countries.…”
Section: Introductionmentioning
confidence: 99%